An investigation into academic burnout, enjoyment and engagement in EFL learning among Chinese junior high school students - Zhang, Xiaohong; Wang, Jian; Ke, Xinli (Frontiers in Psychology, 2024)
With the booming of Positive Psychology, a growing scholarly interest has emerged in language learners’ psychological well-being. However, limited research has been conducted on the emotions of Chinese EFL learners. Therefore, this study aimed to quantitatively examine the burnout, enjoyment, and engagement levels among 387 junior high school EFL learners. The findings revealed that the students experienced low levels of burnout but high levels of enjoyment and engagement in learning. Furthermore, significant gender and grade differences were observed in these variables. The study also found strong negative associations between burnout and both enjoyment and engagement, along with significant positive correlations between enjoyment and engagement. Additionally, it was discovered that enjoyment, rather than burnout, significantly predicted English learning engagement. Interestingly, the study also revealed that enjoyment fully mediated the relationship between engagement and burnout. These findings highlight the importance of promoting enjoyment in order to reduce burnout and foster increased engagement among language learners. This article concludes with the theoretical and pedagogical implications for EFL instruction.